The Pictorial Portrayal of Women and Didactic Messages in the Han and Six Dynasties . - Cheng, Wen-chien (NAN NU -- Men, Women & Gender in Early & Imperial China, 2017)
This study examines the visual forms into which Liu Xiang’s (ca. 79-8 BCE) compilation Lienü zhuan (Categorized biographies of women) were translated during the Han (221 BCE-220 CE) and Six Dynasties (220-589) periods. After Liu Xiang’s work appeared, the images of lienü were established as a distinctive visual category, developed within a broader context of a didactic pictorial genre that engaged the use of images for both the living and the dead. They not only provided admonitory functions, but also were considered auspicious and visually pleasant. In addition to a body of excavated lienü images from these periods, I examine two later scrolls originally rooted in this pictorial genre of lienü, the Lienü renzhi tu (Sympathetic and wise women scroll) in the Palace Museum, Beijing, and the Nüshi zhen tu (Admonitions of the court instructress) in the British Museum. I argue that the two paintings epitomize an ideal female exemplar who is virtuous, graceful, and physically attractive – all these qualities and their textual associations served as markers of the owner/viewer’s elite status.